Corporate Geographical Location and Capital Structure: Evidence from an Emerging Market - Jerbeen, Mohammed; Alnori, Faisal (International Journal of Economics and Financial Issues, 2020)
This study investigates the impact of the geographical location of firms' headquarters on the capital structure decisions of listed non-financial firms in Saudi Arabia. In examining this, we compare the leverage levels among firms ,which their headquarters, are in major and non-major cities in Saudi Arabia. Using a sample of listed non-financial firms over the years 2005–2016 and performing alternative methodologies, we find strong evidence that the location of a firm's headquarters shapes its capital structure choice. Specifically, we find that firms whose headquarters are in major cities have higher market and book leverage levels than firms whose headquarters are in non-major cities (i.e. other cities). This difference is explained by the reason that firms in non-major cities suffer from more information asymmetry and adverse selection problems than other firms, and this therefore makes external debt financing more costly. The outcomes of this study provide important implications for policy makers, investors, and analysts. Keywords: Capital structure, Headquarters' location, Saudi Arabia, Major cities, Non-major cities JEL Classifications: G30, G32, G39 DOI: https://doi.org/10.32479/ijefi.9772